Mechanical properties of Super 304H steel after long-term ageing at 650 and 700°C - Adam Zieliński; Marek Sroka; Hanna Purzyńska; Frantisek Novy (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2023)
The paper shows the degradation process of the modern austenitic Super 304H (X10CrNiCuNb18-9-3) steel which was subjected to long-term aging for up to 50,000 h at 650 and 700°C. The investigations include microstructure examination (SEM), identification and analysis of the precipitation process, and mechanical properties tests. The Super 304H steel has a structure characteristic of austenitic steels with visible annealing twins and single primary NbX precipitates. Long-term aging in the steel leads to numerous precipitation processes of M23C6, MX carbides, σ phase, Z phase, and -Cu phase. Precipitation processes lead to a decrease in plastic properties and impact energy as well as alloy over aging. Yield strength and tensile strength values after 50,000 h of aging were similar to those as delivered. The yield and tensile strength value strongly depend on the applied aging temperature.